2016
DOI: 10.1103/physreve.93.043103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ambient temperature and relative humidity on interfacial temperature during early stages of drop evaporation

Abstract: Understanding drop evaporation mechanisms is important for many industrial, biological, and other applications. Drops of organic solvents undergoing evaporation have been found to display distinct thermal patterns, which in turn depend on the physical properties of the liquid, the substrate, and ambient conditions. These patterns have been reported previously to be bulk patterns from the solid-liquid to the liquid-gas drop interface. In the present work the effect of ambient temperature and humidity during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 36 publications
2
70
0
1
Order By: Relevance
“…Within the studied datasets, Srinagar shows the strongest negative correlation with temperature indicating the reduction in the COVID cases with the increase of temperature and a positive correlation with relative humidity. It has been well established that with the increase in temperature, the relative humidity should drop given that the holding capacity of air will increase [52]. Similar correlations can be seen for Kasaragod and New York.…”
Section: Seir Model Outputsupporting
confidence: 54%
“…Within the studied datasets, Srinagar shows the strongest negative correlation with temperature indicating the reduction in the COVID cases with the increase of temperature and a positive correlation with relative humidity. It has been well established that with the increase in temperature, the relative humidity should drop given that the holding capacity of air will increase [52]. Similar correlations can be seen for Kasaragod and New York.…”
Section: Seir Model Outputsupporting
confidence: 54%
“…Moreover, hydrothermal waves (HTWs) arising due to Marangoni stresses traveling azimuthally from center to the edge of the drop are observed in evaporating alcohol drops [24,25]. Numerous experimental and theoretical studies are recently reported aiming for a further understanding of the physical mechanisms of mentioned HTWs and Marngoni flows within evaporating drops [14,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…It should be pointed out that the isopropanol is semi-transparent to infrared at the wavelengths of (7-14) μm, which means that the temperature distribution captured by the infrared camera is the temperature signature of the liquid layer very close to the droplet surface. Moreover, it is worth mentioning that the infrared thermal imaging technology has been applied in many sessile droplet evaporation researches [22][23][24]. Therefore, it is reliable to capture the surface temperature in present experiments.…”
Section: Experimental Techniquementioning
confidence: 96%